Measuring the Impact of Psychological Trauma Change on Recidivism Among Juvenile Justice–Involved Youth - Tossone, Krystel (Criminal justice and behavior, 2017)
Population heterogeneity and intra-individual change are often overlooked in recidivism research. This study employs latent transition analysis of psychological trauma from intake into a juvenile justice diversion program until termination, followed by modeling of recidivism. A comparison model of a logistic regression without latent variables is also presented, to answer whether the same results would have been achieved without using latent variable modeling. Results indicate that juvenile justice-involved (JJI) youth are assigned into four psychological trauma classes at intake, and three at termination. Latent status membership predicts 6-month recidivism (p = .03). Those who begin in classes that have Depression, Post-Traumatic Stress, and Anger have higher odds of recidivating than those who demonstrate generally high or low trauma symptoms at intake. The comparison regression model found no significant relationship between the five trauma symptom domains and recidivism. Implications for employing latent variable modeling and person-centered analyses for recidivism research are discussed.